Gastric and renal effects of COX-2 selective and non-selective NSAIDs in rats receiving low-dose aspirin therapy - Marcella Goetz MORO; Paula Katherine Vargas SANCHEZ; Mayara Vitorino GEVERT; Emeline Maria BALLER; Ana Flávia TOSTES; Ana Caroline LUPEPSA; Sinvaldo BAGLIE; Gilson Cesar Nobre FRANCO
Abstract The consumption of low-dose aspirin (LDA) to prevent cardiovascular disease continues to increase worldwide. Consequently, the number of chronic LDA users seeking dental procedures that require complementary acute anti-inflammatory medication has also grown. Considering the lack of literature evaluating this interaction, we analyzed the gastric and renal effects caused by a selective COX-2 inhibitor (etoricoxib) and a non-selective COX-2 inhibitor (ibuprofen) nonsteroidal anti-inflammatory drug (NSAID) in rats receiving chronic LDA therapy. Male Wistar rats were divided into six experimental groups (carboxymethylcellulose (CMC) - vehicle; LDA; LDA + ibuprofen; ibuprofen; LDA + etoricoxib; and etoricoxib) and submitted to long-term LDA therapy with a subsequent NSAID administration for three days by gavage. After the experimental period, we analyzed gastric and renal tissues and quantified serum creatinine levels. The concomitant use of LDA with either NSAID induced the highest levels of gastric damage when compared to the CMC group (F = 20.26, p < 0.05). Treatment with either LDA or etoricoxib alone was not associated with gastric damage. No significant damage was observed on kidney morphology and function (F = 0.5418, p > 0.05). These results suggest that even the acute use of an NSAID (regardless of COX-2 selectivity) can induce gastric damage when combined with the long-term use of low-dose aspirin in an animal model. Additional studies, including clinical assessments, are thus needed to clarify this interaction, and clinicians should be careful of prescribing NSAIDs to patients using LDA.